Analysis of retinal flecks in fundus flavimaculatus using optical coherence tomography. Issue 9 (5th June 2006) - Querques, G; Leveziel, N; Benhamou, N; Voigt, M; Soubrane, G; Souied, E H
Abstract : Background/aim: Retinal flecks are commonly observed in both Stargardt disease and fundus flavimaculatus (FFM). The aim was to determine the precise localisation of these flecks within the retinal layers using Stratus optical coherence tomography (OCT). Methods: A prospective observational case series. A complete ophthalmological examination, including autofluorescence, fluorescein angiography (FA), and Stratus OCT (Carl Zeiss) was performed in 49 eyes of 26 consecutive patients with FFM. Six to 12 Stratus OCT linear scans focused on the retinal flecks were performed in each eye. Results: The age at presentation ranged from 23 years to 71 years and visual acuity ranged from 20/20 to 20/400. Hyper-reflective deposits classified into two types were observed on Stratus OCT: type 1 lesions (94% of eyes) presented as dome-shaped deposits located in the inner part of the retinal pigment epithelium (RPE) layer and type 2 lesions (86% of eyes) presented as small linear deposits located at the level of the outer nuclear layer and clearly separated from the RPE layer. Conclusions: Stratus OCT is a non-invasive instrument that provides new information on the location of flecks in FFM. The location of type 2 lesions is quite unusual among macular dystrophies; OCT may therefore be useful in the diagnosis of retinal flecks in some cases of FFM.